PENEGAKAN HUKUM PERAMPOKAN BERSENJATA DI SELAT MALAKA BERDASARKAN HUKUM LAUT INTERNASIONAL - Nabillah Kamila Affandi; Ayu Nrangwesti (Fakultas Hukum Universitas Trisakti, 2023)
Ships traveling through the Malacca Strait are disturbed and harmed by armed piracy, as was the case in 1999 when armed thieves attacked the Alondra Rainbow Ship. The existence of this case serves as an example of how many parties must work together to combat crimes that endanger maritime security; this is a challenge in dealing with armed robberies. The issue at hand is how the law should be applied in the case of the Alondra Rainbow Ship's armed piracy in the Malacca Strait and what legal efforts have been made by Indonesia in relation to armed piracy in the Malacca Strait. The type of research is descriptive, the methodology employed is normative legal research, and data collection is done through library research, data analysis is done qualitatively. The results of research, discussion and conclusions show that the coastal state makes special regulations against crimes at sea, both piracy and robbery. Legal remedies that must be taken, among others, are the division of supervisory authority, increasing security and more equitable development of coastal areas.